2013
DOI: 10.5402/2013/295783
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection Complicating Breast Cancer Surgery in Kuwait

Abstract: Background and Objectives. Surgical site infection (SSI) is the most common postoperative complication associated with breast cancer surgery. The present investigation aimed to determine the SSI rate after breast cancer surgeries and the causative microorganisms. Patients and Methods. All patients who underwent breast surgery in Kuwait Cancer Control Center as a treatment for breast cancer from January 2009–December 2010 were prospectively followed for the development of SSI. Indirect detection was used to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
6
2
Order By: Relevance
“…The rate of seroma for mastectomy patients in other studies has been reported to range between 3 and 85% with an average of 39%, which is higher than the result we have found in our study, which was 17.2% [22,23]. On the contrary, the rate of surgical site infections, 14.9% in our study, was higher in our patient population compared to published reports which ranged between 2 and 6% [24][25][26]. Reports indicated older age, Hypertension, high volume of drainage output, serum protein concentration, longer operative time, and lack of patient-controlled analgesia to be risk factors for seroma formation [23,[27][28][29].…”
Section: Discussioncontrasting
confidence: 91%
“…The rate of seroma for mastectomy patients in other studies has been reported to range between 3 and 85% with an average of 39%, which is higher than the result we have found in our study, which was 17.2% [22,23]. On the contrary, the rate of surgical site infections, 14.9% in our study, was higher in our patient population compared to published reports which ranged between 2 and 6% [24][25][26]. Reports indicated older age, Hypertension, high volume of drainage output, serum protein concentration, longer operative time, and lack of patient-controlled analgesia to be risk factors for seroma formation [23,[27][28][29].…”
Section: Discussioncontrasting
confidence: 91%
“…Moreover, the retrospective nature of the majority of the studies may have influenced the SSI rate recorded, possibly resulting in higher rates due to follow-up being conducted on an outpatient basis. If an SSI developed but did not require readmission then it may not have been documented in the patient records, meaning it was not included in the study [16,76]. Almost one-third of the studies had a follow-up period of one month, owing to the fact that an SSI is typically defined as occurring within the 30-day time period after surgery [168].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to local wound care, empiric treatment with systemic antibiotics to cover Pseudomonas species should be considered for those women who later present with postoperative wound infection. Although colonization of chronic and malignant wounds with Pseudomonas species has been well described, the association between postoperative Pseudomonas species wound infections and pre‐existing malignant breast wounds is less known . The study reminds us that we can all learn from one another and that funding for research in distant settings may generate findings applicable to local situations.…”
mentioning
confidence: 87%
“…14 The authors reported that women who presented with fungating tumors were more likely to have postoperative wound infections than women who did not and that with Pseudomonas species has been well described, the association between postoperative Pseudomonas species wound infections and preexisting malignant breast wounds is less known. [15][16][17] The study reminds us that we can all learn from one another and that funding for research in distant settings may generate findings applicable to local situations.…”
mentioning
confidence: 91%